2015
DOI: 10.1016/j.theriogenology.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and transplantation of sturgeon early-stage germ cells

Abstract: We report, for the first time, a series of baseline techniques comprising isolation and transplantation of female and male early-stage germ cells in sturgeon to generate a germline chimera as a potential tool for surrogate reproduction and gene banking. Cells were dissociated from testis, characterized by mostly spermatogonia, and from ovary, exclusively comprising oogonia and previtellogenic oocytes, of Acipenser baerii, using 0.3% trypsin (2 hours, 23 °C) dissolved in PBS, isotonic with blood plasma. The dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(51 citation statements)
references
References 25 publications
2
46
0
3
Order By: Relevance
“…Moreover, a PGC transplantation assay between sturgeon and goldfish proved that PGC migration machinery is conserved between these two distantly related species (Saito et al 2014). The ability of chimeric mRNA to label and trace PGCs in Dabry's sturgeon is extremely useful for PGC cryopreservation and the conservation of endangered species by germ cell transplantation technologies (Okutsu et al 2006;Psenicka et al 2015;Saito and Psenicka 2015;Yoshizaki et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a PGC transplantation assay between sturgeon and goldfish proved that PGC migration machinery is conserved between these two distantly related species (Saito et al 2014). The ability of chimeric mRNA to label and trace PGCs in Dabry's sturgeon is extremely useful for PGC cryopreservation and the conservation of endangered species by germ cell transplantation technologies (Okutsu et al 2006;Psenicka et al 2015;Saito and Psenicka 2015;Yoshizaki et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility is the transplantation of subsequent stages of PGCs, the SG/OG. The advantage of SG/OG in comparison with PGCs is in their easy isolation from testes or ovary to obtain a large number of cells which can be directly microinjected into the body cavity of recipient fry to counteract the potential migration inability of transplanted germ cells [23,25]. To induce germ line chimera producing donor's gametes only, the host should be sterile.…”
Section: Importance Of Germ Cellsmentioning
confidence: 99%
“…We have already shown that sturgeon PGCs can be isolated using an enzymatic solution and the isolated cells can be transplanted into different species; furthermore, transplanted PGCs can migrate to the genital ridge even in a phylogenetically distant xenogeneic host [18]. Additionally, we established a technique for isolating spermatogonia and oogonia using Percoll gradient layers; transplantation of these cells into the body cavity of hatched larvae showed that they can proliferate, migrate and settle at the host gonadal ridge [36]. In this transplantation experiment, the PGCs of the host were labeled with FITC, while the transplanted donor germ cells were labeled with the common cell-labeling reagent PKH-26; this allowed us to check that the donor PGCs localized to the developing host gonad.…”
Section: Discussionmentioning
confidence: 99%